Cardiac Lymphatics: An Example of Systems Biology in Medicine - Bland, Jeffrey (Integr Med (Encinitas), 2017)
When evaluated from the 2017 perspective, the 1981 Lemole cardiac lymphatic drainage model for the origin of atherosclerosis appears very prescient. The concept proposed by Dr Lemole is rooted in a systems biology understanding of the origin of disease (itself a very novel concept in 1981). The Lemole hypothesis for the origin of atherosclerosis pioneered the application of systems thinking in cardiology and brought the importance of lifestyle factors and physical medicine approaches for the prevention and treatment of cardiac disease to the threshold of a mechanistic understanding. It is this type of systems biology approach to clinical problem solving that forms the heuristic of the functional medicine model.